Daptomycin (Cubicin) in patients with complicated skin or soft-tissue infections - Sacchi, Viola (Farmeconomia. Health economics and therapeutic pathways, 2008)
Skin and soft-tissue infections (SSTIs) are commonly observed and differ in terms of site and localization, clinical characteristics, and the aetiological agent; these infections are usually caused by Staphylococcus aureus or beta-haemolytic streptococci, and are the most frequent forms of methicillin-resistant S. aureus (MRSA) infections. SSTIs are considered complicated if they involve deeper skin structures (fascia or muscle layers), require significant surgical intervention or arise in the presence of significant co-morbidity. The progressive increase of bacterial resistance, in particular for Gram-positive bacteria infections, to currently used agents is a serious and growing problem, and in particular MRSA, GISA (glycopeptides-insusceptible S. aureus), VRE and GRE (glycopeptides-resistant enterococci) are of concern. There is, therefore, a need for additional agents active against these difficult-to-treat pathogens.